Recurrent Streptococcus equi subsp. zooepidemicus Bacteremia in an Infant - Watson, Joshua R. (J Clin Microbiol, 2015)
We describe a case of an infant with recurrent bacteremia caused by Streptococcus equi subsp. zooepidemicus, likely transmitted from mother to infant. Our case highlights the importance of an epidemiological history and molecular diagnostics in ascertaining insights into transmission, pathogenesis, and optimal management.